VOX’s victory in Region of Murcia: the discourse of the party’s leaders and voters - Moreno Moreno, Salvador (Política y Sociedad, 2023)
The last Spanish general election on 10th November 2019 are remarkable due to the outstanding results of the emerging Spanish political party VOX. VOX’s votes specially took off in the Region of Murcia, taking the most seats provided by this Autonomous Community to the Spanish Parliament. This research aims to explore this political party in the Region of Murcia comparing VOX’s discourse with their voters’ discourse and thoughts through the hypothesis-generating case study method. To do so, we analysed VOX’s discourse in the Region of Murcia following Critical Discourse Analysis (CDA) methods. Lastly, we compared that analysis with VOX’s voters’ discourse and thoughts, which were collected by means of group discussions. Results confirm a resemblance between VOX’s leaders and their voters’ discourse in Murcia. Keywords: VOX; discourse; Region of Murcia; far-right wing; elites and mass.